Efek Pemberian Sports Drinks dengan Tambahan Kulit Terong Ungu (Solanum melongena, L.) Terhadap Indeks Kelelahan Otot - Mahsa Ulima, Rayna; Lestari, Yanesti Nuravianda (NUTRIZIONE - Nutrition Research and Development Journal, 2024)
Volleyball is a sport that involves intense physical activity, which has the potential to trigger oxidative stress due to an imbalance between the production of free radicals and antioxidants in the body. This imbalance can cause oxidative stress in the muscles and lead to muscle fatigue (Luthfi et al., 2023). Purple eggplant skin (Solanum melongena, L.) is known to be rich in anthocyanins, which can reduce oxidative stress and accelerate post-exercise muscle recovery. This study focused on the effects of sports drink with added eggplant skin (Solanum melongena, L.) on muscle fatigue index. This study was conducted with a quasi-experimental approach using a pretest-posttest control group design with the same subject. The research subjects consisted of 17 athletes, where the control group received a placebo and the experimental group was given sports drink with added purple eggplant skin (Solanum melongena, L.). Measurements taken in this study include body weight, height, food intake, physical activity, and muscle fatigue levels. The results of the mann whitney test showed no difference in the muscle fatigue index of volleyball athletes between the control and experimental groups after treatment with a P value of 0.326 (p>0.05). The wilcoxon test showed no difference in muscle fatigue index before and after treatment in the control group with a P value of 0.344 (p>0.05) and there was a difference in muscle fatigue index before and after treatment in the experimental group with a P value of 0.041 (p>0.05).